Pemeliharaan dan Inventarisasi Alat serta Bahan Laboratorium dalam Mendukung Pembelajaran di Sekolah Dasar - Imam Ahyar; Junaidin (Mataram University, 2026)
Maintenance of laboratory equipment and materials is a crucial activity in laboratory management, ensuring the smooth running of practicums, occupational safety, and the quality of learning and research outcomes. This study aims to examine the importance of maintaining laboratory equipment and materials, its implementation procedures, and the benefits it provides in supporting the effectiveness of laboratory activities. The research method used was library research with a qualitative descriptive approach. Data were obtained through a review of various literature sources, including books, scientific journal articles, official documents, and regulations related to laboratory management. Data analysis techniques included collection, reduction, presentation, and drawing conclusions from various relevant sources. The results indicate that laboratory equipment maintenance includes cleaning, storage, periodic inspections, calibration, and repair to maintain function and accuracy. Meanwhile, laboratory material maintenance includes labeling, storage according to material characteristics, monitoring expiration dates, and safe waste management. This study also indicates that proper maintenance plays a crucial role in increasing the efficiency of laboratory facilities, reducing the risk of equipment damage and workplace accidents, and supporting the success of practicums and research activities. Maintenance success is influenced by human resource competence, the availability of standard operating procedures (SOPs), an integrated inventory system, and adequate budget support. Therefore, implementing a planned and sustainable maintenance system is a crucial factor in creating a safe, effective, efficient, and high-quality laboratory.